PENGARUH PENAMBAHAN KONSENTRAT DENGAN KADAR PROTEIN KASAR YANG BERBEDA PADA RANSUM BASAL TERHADAP KECERNAAN BAHAN KERING DAN KECERNAAN BAHAN ORGANIK KAMBING BOERAWA PASCA SAPIH - Muhamad Nur Kundau; Liman .; Syahrio Tantalo (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The experiment was conducted for 1 mounth from 27th August to 26th September 2012, in the village of Campang, District Gisting, Regency of Tanggamus. Goats are used is pasca-weaning Boerawa goat as many as 20 goats with an average initial weight of 18,25 ± 6,13 kg/goats. This research used randomized block design, consisting of four treatments, with repeated five times, they are R0: bassal feeding, R1: bassal feeding + concentrate (Crude Protein 13%), R2: bassal feeding + concentrate (CP 16%), and R3: bassal feeding + concentrate (CP 19%). The results shows: (1) a significant effect (P <0.05) additions concentrates on bassal feeding to organic matter digestibility Boerawa goats pasca-weaning, the opposite effect was not significant (P>0.05) for dry matter digestibility, and (2) the best effect of the addition of concentrates in the bassal feeding to organic matter digestibility.